1989
DOI: 10.1007/bf01870850
|View full text |Cite
|
Sign up to set email alerts
|

Conduction and blocking properties of a predominantly anion-selective channel from human platelet surface membrane reconstituted into planar phospholipid bilayers

Abstract: We have investigated the basic properties of a predominantly anion-selective channel derived from highly purified human platelet surface membrane. Single channels have been reconstituted into planar phospholipid bilayers by fusion of membrane vesicles and recorded under voltage-clamp conditions. The channel is found to have the following properties: (i) Channel activity occurs in bursts of openings separated by long closed periods. (ii) The current-voltage relationship is nonlinear. Channel current is seen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…In most previous planar bilayer studies of small conductance CI-channels, the observed I-V behavior exhibited a characteristic negative rectification (i.e., trans---, cis CI-flux is less than cis ~ trans CI-flux) (Coronado and Latorre, 1982;Reinhardt et al, 1987;Bridges et al, 1989;Manning and Williams, 1989). In the case of colon epithelia, a similar outward-rectifying CI-channel is known to exist in the intact tissue (Halm et al, 1988).…”
Section: Permeation and Gating Characteristics Distinguish Two Major mentioning
confidence: 91%
See 2 more Smart Citations
“…In most previous planar bilayer studies of small conductance CI-channels, the observed I-V behavior exhibited a characteristic negative rectification (i.e., trans---, cis CI-flux is less than cis ~ trans CI-flux) (Coronado and Latorre, 1982;Reinhardt et al, 1987;Bridges et al, 1989;Manning and Williams, 1989). In the case of colon epithelia, a similar outward-rectifying CI-channel is known to exist in the intact tissue (Halm et al, 1988).…”
Section: Permeation and Gating Characteristics Distinguish Two Major mentioning
confidence: 91%
“…Since some Cl-channels exhibit a significant permeability for monovalent cations (Franciolini and Nonner, 1987) including TEA + (Manning and Williams, 1989), we examined the effect of TEA + on the lobster Cl-channel. Fig.…”
Section: Asymmetric Current Inhibition By Teamentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of ATP to the extracellular side caused a dosedependent, flickery-type blockade of reconstituted rectifying CI-channels obtained from airway epithelial cells and platelets with an estimated ICs0 of 40 IxM (Manning and Williams, 1989;Alton et al, 1991). Blockade by extracellular ATP is not limited to reconstituted channels since Stutts, Chinet, Mason, Fullton, Clarke, and Boucher (1992) have presented data showing that external ATP increased burst duration of rectifying C1-channels in excised apical membrane patches from airway epithelial cells, which is the result expected if ATP is acting as a fast or flickery-type blocker.…”
Section: Introductionmentioning
confidence: 97%
“…Chloride channels in excised, inside-out membrane patches from human platelets Amanda B. MacKenzie and Martyn P. Mahaut-Smith Physiological Laboratory, Downing Street, Cambridge CB2 3EG Anion-selective channels have been previously reported in human platelet membranes (Manning & Williams, 1989;Mahaut-Smith, 1990), yet their importance in platelet responses remains unknown. To date, only one study has used patch-clamp techniques to record platelet Cl-currents, however, these whole-cell recordings (Mahaut-Smith, 1990) provided only limited information due to the lack of control over the cytosolic environment.…”
mentioning
confidence: 99%